(untitled) (Proceedings of the International Conference on Social Sciences, 2023)
Over the past decade, many new words besides "Information literacy" in higher education have been defined. This results from innovations or new technologies that change lifestyles, known as Digital/Technology disruption. Information literacy research may be replaced by new literacies. To examine the situation and trends of information literacy research in higher education, the researcher collected information literacy research articles in higher education in Asia countries for the period 2010 – 2021 which indexed the Web of Science’s SSCI (Social Sciences Citation Index) database with keywords related to “information literacy in higher education” (ILHE) and conducted the analysis using bibliographic mapping and content analysis. To identify characteristics (research journals, sample group, research methods, research domains), various distributions (the most cited articles, most popular keywords, the most cited journals (citation and co-citation), the most-cited authors (citation and co-citation)), and the most used keywords in the articles related to the use of information literacy in higher education for the period 2010 – 2021. The results found that there is persisting on information literacy in higher education. It is not replaced by new skills or new literacies. But there is some overlap between other cognitive skills. However, terms such as digital literacy, media literacy, and multiliteracy have emerged over the 12 years of research studies. Additionally, The Framework for Information Literacy for Higher Education (FILHE) is also the primary standard framework used to refer to as a framework for teaching and learning information literacy in higher education.